Corporate Social Responsibility, Kinerja Lingkungan, Dan Nilai Perusahaan - Hansel, Richard; Narsa, Niluh Putu Dian Rosalina Handayani; Sriani, Dewi (ACE: Accounting Research Journal, 2025)
This study aims to empirically examine the influence of Corporate Social Responsibility on firm values and the moderating effect of enviromental performance on the influence of CSR and firm value. This study uses companies of the food and beverage sub-sector manufacturing industry as a sample with the observation year between 2017-2020. The analytical method uses in this study is the multiple linear regression analysis and residual test through the SPSS 25 application. The results of this study indicate that CSR has a negative effect on firm values, however environmental performance is found does not moderate the effect of CSR on firm values. It can be concluded that the majority of companies in making CSR are still far from the applicable GRI G4 standards .